Análise de medidas e práticas de eficiência energética aplicadas em um supermercado - Fernandes, Yuri Yamada (2020)
This work consists in proving the increase in the price of electricity and consumption growth, justifying the importance in projects that seek to increase energy efficiency of installations. A large portion of a supermarket's spending comes from the electricity because it has food preservation refrigeration systems and lighting throughout the operating period. The increased demand for distributed generation, mainly photovoltaic solar panels, are indications of the great concern of residential, commercial and industrial consumers to reduce their energy expenses. In addition to changes in installations, it is also necessary to analyze the impacts of tariff flags and service category change to justify the improvements through calculations that prove the economy viability of investments.